Conflict Management Strategies: The Role of Personality and Specific Social Relation Beliefs in Serbia and Italy - Dzamonja Ignjatovic, Tamara Z; Petrović, Danijela S.; Kosić, Ankica; Dimoski, Jana; Knežević, Goran (Psihološka istraživanja, 2025)
This study explored the relationships among conflict management strategies, personality traits, and beliefs about social relations in Italy and Serbia, countries that are geographically close but have different histories, traditions, and religions and differ along an individualistic-collectivistic dimension. Goals: The study aimed to explore and compare how basic personality dimensions predict specific conflict management strategies and how the Competitive Jungle worldview and beliefs about conflicts mediate their relationship in different cultures. Method: The sample comprises 764 young people, aged 18-30 (M=21.54, SD=2.80). Measures included the Dutch Test of Conflict Handling, Mini IPIP-6, Delta personality inventories, Competitive Jungle Worldview, and Conflict Beliefs scales. Path analyses were applied with seven personality traits as predictors (Neuroticism, Extraversion, Openness, Agreeableness, Conscientiousness, Honesty, and Disintegration), two social relation beliefs as mediators, and three conflict management strategies (Cooperative, Defensive, and Competitive), as criterion variables. Results: Results show that common predictors were Openness and Agreeableness for Cooperative strategies, Agreeableness and Disintegration for Defensive strategies, and Extraversion for Competitive strategies. Neuroticism and Conscientiousness were not implicated in conflict situations, while Honesty and Disintegration have different impacts on that behavior in the two cultures. Results confirmed different pathways of personality traits through the beliefs about the world as a competitive jungle and conflicts as threats or challenges. Conclusion: Basic personality traits, as universal dispositions for behavior, have similar effects on conflict management strategies in both countries, while differences are observed in the mediating role of beliefs, which are shaped by cultural differences between Serbia and Italy.